STEREOTIP MAHASISWI BERCADAR DAN REAKSINYA TERHADAP MAHASISWI STAI MUHAMMADIYAH PROBOLINGGO - Reza Hilmy Luayyin; Aulia Rahman; Imanuddin Abil Fida (USRAH: Jurnal Hukum Keluarga Islam, 2023)
This paper aims to find out the forms of stereotypes obtained by students as well as to be able to understand the reactions of niqab students due to the negative stereotypes they get. There are some students who wear the niqab but almost all niqab students have received negative stereotypes both from internal campus and from external campus. The methodology used in this research uses a descriptive qualitative approach that describes the nature of something that is happening at the time of research and examines the cause of two symptoms. The data obtained from observations and interviews show that the negative stereotypes that female students get vary in form, including being said to be pretentious, said to look like ninjas, like terrorists, radical jama'ah, just following the trend, and following their parents. The reactions of veiled female students due to negative stereotypes also vary, including the majority of those who wear the veil being ordinary and indifferent to the negative stereotypes labeled to them. Although there is a slight sense of disappointment and sadness, they are even mature and positive thinking while still praying for those who label negatively so that they will soon realize and understand.